Factors that Influence Intention to use Mobile Banking - Setiawan, Steffi Odelia; Dipa Mulia (Dinasti Publisher, 2023)
The increase in internet penetration in Indonesia which has reached 77.02% is not in line with the growth of Bank Mandiri mobile banking users to the number of customers which is still low. This study evaluates perceived ease of use, trust, compatibility, security, and convenience on intention to use m-banking with the mediation of perceived usefulness. This study distributed online questionnaires collected through social media and obtained 210 respondents in the Jabodetabek area. This research method uses quantitative with the Partial Least Square (PLS) - Structural Equation Modeling (SEM) method using the Smart PLS 3.0 program. The results state that perceived usefulness affects intention to use m-banking, perceived ease of use and trust affect perceived usefulness. Perceived usefulness variables can mediate perceived ease of use and trust in intention to use m-banking.